The complete sequence of a full length cDNA for human liver glyceraldehyde-3-phosphate dehydrogenase: evidence for multiple mRNA species. - Arcari, P (1984)
A recombinant M13 clone (O42) containing a 65 b.p. cDNA fragment from human fetal liver mRNA coding for glyceraldehyde-3-phosphate dehydrogenase has been identified and it has been used to isolate from a full-length human adult liver cDNA library a recombinant clone, pG1, which has been subcloned in M13 phage and completely sequenced with the chain terminator method. Besides the coding region of 1008 b.p., the cDNA sequence includes 60 nucleotides at the 5'-end and 204 nucleotides at the 3'-end up to the polyA tail. Hybridization of pG1 to human liver total RNA shows only one band about the size of pG1 cDNA. A much stronger hybridization signal was observed using RNA derived from human hepatocarcinoma and kidney carcinoma cell lines. Sequence homology between clone 042 and the homologous region of clone pG1 is 86%. On the other hand, homology among the translated sequences and the known human muscle protein sequence ranges between 77 and 90%; these data demonstrate the existence of more than one gene coding for G3PD. Southern blot of human DNA, digested with several restriction enzymes, also indicate that several homologous sequences are present in the human genome.